IMPLEMENTASI DIFUSI INOVASI PROGRAM VASEKTOMI KOTA SURABAYA - Hilda Yunita Wono; Hadassah Elisha Karsten; Agung Prasetyo (Universitas Gunadarma, 2022)
The population density in Surabaya which continues to increase needs to be accompanied by an increase in population community participation in the Family Planning (KB) program. Currently, most family planning programs are run by women, with a high level of risk that can lead to death. Findings related to family planning in men or vasectomy are far better options for dealing with this. However, what happens is that the vasectomy participation rate is still too low. Therefore, Dinas Pemberdayaan Perempuan dan Perlindungan Anak serta Pengendalian Penduduk dan KB in the City of Surabaya has intensively carried out socialization of the vasectomy program. This study wants to see the implementation of the diffusion of Everett M. Rogers innovation carried out by Dinas Pemberdayaan Perempuan dan Perlindungan Anak serta Pengendalian Penduduk dan KB in the process of socializing the vasectomy program to increase vasectomy acceptors. The research method was carried out quantitatively with an online survey. The results of this study indicate that Dinas Pemberdayaan Perempuan dan Perlindungan Anak serta Pengendalian Penduduk dan KB in the City of Surabaya has carried out four elements in the implementation of the diffusion of innovation, namely innovation material, communication channels, time period and social system. This is shown from 15 indicators, 9 of which answered 100% on the highest Likert scale, which is very appropriate. This happened because the Of ice of Women's Empowerment and Child Protection as well as Population Control and Family Planning explained various things related to vasectomy according to the expectations of the acceptors.